CUSTARD, CULVERTS AND CAKE : academics on life in the archers. (EMERALD Group PUBL, 2017)
Leading scholars from the Academic Archers network combine a love of The Archers with their specialist subjects, in Custard, Culverts and Cake - a sometimes serious, but most often wry look at the people of Ambridge. Scholars take on subjects such as food, geography, social media, faith and naturally, the Helen and Rob storyline.